A new emission inventory for nonagricultural open fires in Asia from 2000 to 2009 - Song, Yu; Chang, Di; Liu, Bing; Miao, Weijie; Zhu, Lei; Zhang, Yuanhang (Environmental research letters, 2010)
Open fires play a significant role in atmospheric pollution and climatic change. This work aims to develop an emission inventory for nonagricultural open fires in Asia using the newly released MODIS (Moderate Resolution Imaging Spectroradiometer) burned area product (MCD45A1), as the MODIS sensor cannot efficiently detect field crop residue burning. Country-level or province-specific biomass density data were used as fuel loads. Moisture contents were taken into account when calculating combustion factors for grass fuel. During the nine fire years 2000–2008, both burned areas and fire emissions clearly presented spatial and seasonal variations. Extensive nonagricultural open fires were concentrated in the months of February and March, while another peak was between August and October. Indonesia was the most important contributor to fire emission, which was largely attributable to peat burning. Myanmar, India, and Cambodia together contributed approximately half of the total burned area and emission. The annual emissions for CO 2 , CO, CH 4 , NMHC s , NO x , NH 3 , SO 2 , BC, OC, PM 2.5 , and PM 10 were 83 (69–103), 6.1 (4.6–8.2), 0.38 (0.24–0.57), 0.64 (0.36–1.0), 0.085 (0.074–0.10), 0.31 (0.17–0.48), 0.030 (0.024–0.037), 0.023 (0.020–0.028), 0.27 (0.22–0.33), 2.0 (1.6–2.6), and 2.2 (1.7–2.9) Tg yr − 1 , respectively. This inventory has a daily temporal resolution and 500 m spatial resolution, and covers a long period, from April 2000 to February 2009. It could be used in global and regional air quality modeling.